Investigation of Undergraduate Nursing Students’ Readiness to Practice in the UAE - AL MEKKAWI, MOHAMED (2019)
Mounting concerns raised in the last few decades on the ability of educational providers and health care facilities to maintain adequate levels of collaboration and cooperation to graduate work-ready nursing students. The claims on the adequacy of education programs and clinical training experiences of nursing students exerted unremitting challenges for both nursing education providers and health care facilities in many countries. The purpose of the study is to investigate undergraduate nursing students’ readiness to practice in the UAE and identify factors that foster or hinder their readiness to practice during students’ clinical training experiences. The study followed a sequential exploratory mixed method design that began with collecting qualitative data from 19 nursing students in their final year of study, four faculty members, and three hospital education leaders using focus group and semi-structured interviews. Quantitative data was then collected during the second phased from a larger group of nursing students. Quantitative data was collected from 90 nursing students in their final year of study at five different nursing colleges using Casey-Fink Readiness to Practice Survey 2008. The survey examined students’ level of confidence to perform specific clinical practice skills to analyze their perceived readiness to practice. Data analysis revealed that most of the participants perceived that they are ready to practice registered nurse role after graduation. Many students expressed that they are not confident enough to take care for more than 2-3 patients and highlighted that they are not comfortable enough to practice some nursing skills such as Chest tube care, Code response, IV insertion/removal, Trach care, NG insertion, and Catheter insertion. The study had numerous implications for nursing education in the UAE and the region.